The Effectiveness of Motion Exploration Learning Media in Training Basic Locomotor Movements of Elementary School Students - Rahma Dewi; Indra Kasih; Efrida Eriani Hasibuan; Muhammad Reza Destya; Bessy Sitorus Pane (Program Studi Pendidikan Kepelatihan Olahraga Fakultas Ilmu Pendidikan Universitas Bhayangkara Jakarta Raya, 2026)
This study was motivated by the low level of fundamental locomotor skills among elementary school students, which was influenced by the limited variation and innovation in physical education learning media. The study aimed to examine the effectiveness of movement exploration learning media in improving students’ locomotor skills. A quantitative experimental method with a pretest and posttest control group design was employed. The participants consisted of 30 elementary school students who were divided into an experimental group and a control group. The instrument used was a locomotor skill test covering walking, running, jumping, and hopping. Data were analyzed using statistical tests to compare improvements between groups. The results showed a significant increase in locomotor skills in both groups, with the experimental group demonstrating higher improvement than the control group. The findings indicated that movement exploration learning media effectively enhanced students’ active participation and improved learning outcomes in physical education. The novelty of this study lies in the application of exploration based learning media that provides contextual and enjoyable movement experiences for elementary school students.